Anti-inflammatory effect of Barringtonia angusta methanol extract is mediated by targeting of Src in the NF-κB signalling pathway. (1st January 2021) - Jo, Minkyeong; Lee, Jongsung; Kim, Han Gyung; Kim, Jin Kyeong; Kim, Haeyeop; Shin, Kon Kuk; Bach, Tran The; Eum, Sang Mi; Lee, Jong Sub; Choung, Eui Su; Yang, Yoonyong; Kim, Kyung-Hee; et al.
Abstract: Context: Among the plants in the genus Barringtonia (Lecythidaceae) used as traditional medicines to treat arthralgia, chest pain, and haemorrhoids in Indonesia, Barringtonia racemosa L. and Barringtonia acutangula (L.) Gaertn. have demonstrated anti-inflammatory activity in systemic inflammatory models. Objective: The anti-inflammatory activity of Barringtonia angusta Kurz has not been investigated. We prepared a methanol extract of the leaves and stems of B. angusta (Ba-ME) and systemically evaluated its anti-inflammatory effects in vitro and in vivo . Materials and methods: RAW264.7 cells stimulated with LPS or Pam3CSK4 for 24 h were treated with Ba-ME (12.5, 25, 50, 100, and 150 µg/mL), and NO production and mRNA levels of inflammatory genes were evaluated. Luciferase reporter gene assay, western blot analysis, overexpression experiments, and cellular thermal shift assay were conducted to explore the mechanism of Ba-ME. In addition, the anti-gastritis activity of Ba-ME (50 and 100 mg/kg, administered twice per day for two days) was evaluated using an HCl/EtOH-induced gastritis mouse model. Results: Ba-ME dose-dependently suppressed NO production [IC50 = 123.33 µg/mL (LPS) and 46.89 µg/mL (Pam3CSK4)] without affecting cell viability. Transcriptional expression of iNOS, IL-1β, COX-2, IL-6, and TNF-α and phosphorylation of Src, IκBα, p50/105, and p65 were inhibited by Ba-ME. The extract specifically targeted the Src protein by binding to its SH2 domain. Moreover, Ba-ME significantly ameliorated inflammatory lesions in the HCl/EtOH-induced gastritis model. Discussion and Conclusions: The anti-inflammatory activity of Ba-ME is mediated by targeting of the Src/NF-κB signalling pathway, and B. angusta has potential as an anti-inflammatory drug.